Feeding ecology of freshwater fishes in tropical rivers (Zoological Records and Reviews, 2023)
Feeding ecology underpins the functional role of fish species within riverine food webs and determines the trophiclinkages that regulate energy flow and nutrient cycling in freshwater ecosystems. Tropical rivers, characterised by highfish diversity, strong seasonal hydrological variability, and complex lateral connectivity between river channels andfloodplain habitats, present distinctive feeding ecology challenges and opportunities for diverse fish communities. Thisstudy examines the feeding ecology of 84 freshwater fish species from the Godavari and Krishna river systems ofpeninsular India, using stomach content analysis, stable isotope analysis (delta13C and delta15N), and functional traitassessment at 18 sites sampled during monsoon flood and dry season low-flow periods over two years (2021-2023).Fish species are classified into eight feeding guilds based on stomach content analysis. Piscivores and invertivoresdominate in terms of biomass contribution; algal grazers and detritivores are most species-rich. Stable isotope analysisreveals significant seasonal shifts in diet composition, with 38.4% of species showing ontogenetic diet shifts frominvertivory to piscivory or herbivory. Invasive tilapia (Oreochromis niloticus) occupies a broad trophic niche that overlapssignificantly with native species, with measured trophic overlap values exceeding 0.7 for 12 native species. Conservationimplications of trophic disruption by invasive species and by water quality changes affecting food web structure arediscussed.
Keywords: tropical rivers; food web; tilapia invasion; trophic guild; Krishna river; Godavari; stable isotopes; stomach content analysis; freshwater fish; feeding ecology